Glow in the Dark: Using a Heat-Sensitive Camera for Blind Individuals with Prosthetic Vision - Sadeghi, Roksana (Vision Res, 2021)
To date, retinal implants are the only available treatment for blind individuals with retinal degenerations such as retinitis pigmentosa. Argus II is the only visual implant with FDA approval, with more than 300 users worldwide. Argus II stimulation is based on a grayscale image coming from a head-mounted visible-light camera. Normally, the 11° × 19° field of view of the Argus II user is full of objects that may elicit similar phosphenes. The prosthesis cannot meaningfully convey so much visual information, and the percept is reduced to an ambiguous impression of light. This study is aimed at investigating the efficacy of simplifying the video input in real-time using a heat-sensitive camera. Data were acquired from four Argus II users in 5 stationary tasks with either hot objects or human targets as stimuli. All tasks were of m-alternative forced choice design where precisely one of the m ≥ 2 response alternatives was defined to be “correct” by the experimenter. To compare performance with heat-sensitive and normal cameras across all tasks, regardless of m, we used an extension of signal detection theory to latent variables, estimating person ability and item difficulty in d′ units. Results demonstrate that subject performance was significantly better across all tasks with the thermal camera compared to the regular Argus II camera. The future addition of thermal imaging to devices with very poor spatial resolution may have significant real-life benefits for orientation, personal safety, and social interactions, thereby improving quality of life.